Management of English Speaking Learning at SMK Muhammadiyah 1 Blora - Driyono, Djoko; , Prof. Dr. Yetty Sardjono, M.Si; , Dra. Dwi Haryanti, M. Hum (2013)
This study entitled Management of English Learning of Speaking: A site Study at SMK Muhammadiyah 1 Blora has expected goal: 1) to describe the learning plan English speaking. 2) to describe the implementation of English learning of speaking. 3)to describe the evaluation of English learning of speaking. 4) to describe the follow-up assessment of learning outcomes English speaking. Research appiroach is ethnography qualitative. Data collection methods included observation, in-depth interviews, documentation. Validity of the data obtained with trianggulation, review informant. Technigues in data analysis through the (1) data reduction (2) data presentation (3) drawing conclusions and verification. The research result can conclude that manage English Learning of speaking in SMK Muhammadiyah 1 Blora by using learning plan early semester. Learning Plan consists syllabus and lesson plan (RPP), that included speaking skill. Learning Implementation base on RPP that is made by English teacher, consist of speaking material every english lesson. Learning Implementation process was done by giving speaking material, so students can easy to speak English very well. Learning Evaluation include: pronounciation, content, performances,and grammar during learning process, and the follow-up Assesment of Speaking conductedafter the teacher gave an evaluation at the end of learning.